ANALISIS MEDIA PAPAN JURANG DALAM MENINGKATKAN PEMAHAMAN KONSEP ARITMATIKA DASAR DI MADRASAH IBTIDAIYAH - Nurhidayah Nurhidayah; Khurinin Ratnasari (STKIP Singkawang, 2025)
This study is based on the lack of students' ability to understand counting operations, inappropriate learning approaches and minimal use of appropriate media. The purpose of this study was to analyze the effectiveness of the deep ravine board media, improving the understanding of basic arithmetic concepts in class II students of MI Bustanul Ulum 06. The method applied was quantitative through a pretest-posttest experimental design, the population in the study consisted of all students of MI Bustanul Ulum 06 with a sample of 18 students taken through the simple random sampling method. Data collected through observation, interviews, questionnaires and documentation, and analyzed through validity, reliability, normality and paired t-test tests. The findings of the study describe the deep ravine board media has an effect on improving the understanding of basic arithmetic concepts. Referring to the findings of the paired t-test that the 2-tailed sig score of 0.01 for understanding basic arithmetic concepts 0.01 for stacked addition and 0.01 for stacked subtraction are all <0.05. This indicates that the use of the ravine board media is effective in improving students' understanding of addition and subtraction operations in grade II students at MI Bustanul Ulum 06 Krebet. The conclusion that can be drawn from this study is that the ravine board media can develop more interactive, interesting learning and increase student participation in understanding basic arithmetic concepts.